2015
DOI: 10.1088/0004-637x/815/2/121
|View full text |Cite
|
Sign up to set email alerts
|

AHUBBLEDIAGRAM FROM TYPE II SUPERNOVAE BASED SOLELY ON PHOTOMETRY: THE PHOTOMETRIC COLOR METHOD

Abstract: We present a Hubble diagram of type II supernovae using corrected magnitudes derived only from photometry, with no input of spectral information. We use a data set from the Carnegie Supernovae Project I (CSP) for which optical and near-infrared light-curves were obtained. The apparent magnitude is corrected by two observables, one corresponding to the slope of the plateau in the V band and the second a colour term. We obtain a dispersion of 0.44 mag using a combination of the (V − i) colour and the r band and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 98 publications
5
73
2
1
Order By: Relevance
“…Anderson et al (2014) found that more luminous SNeII have higher s 2 (steeper decline, >1.15 mag per 100 days), confirming previous studies finding that traditional SNeIIL are more luminous than SNeIIP (Patat et al 1994;Richardson et al 2014). Using this correlation and adding a color term, de Jaeger et al (2015) succeeded in reducing the scatter in the low-redshift SNeII Hubble diagram ( = z 0.01 0.04 -) to a level of ∼0.4 mag (±0.05 mag), which corresponds to a precision of 18% in distances.…”
Section: Introductionsupporting
confidence: 76%
See 3 more Smart Citations
“…Anderson et al (2014) found that more luminous SNeII have higher s 2 (steeper decline, >1.15 mag per 100 days), confirming previous studies finding that traditional SNeIIL are more luminous than SNeIIP (Patat et al 1994;Richardson et al 2014). Using this correlation and adding a color term, de Jaeger et al (2015) succeeded in reducing the scatter in the low-redshift SNeII Hubble diagram ( = z 0.01 0.04 -) to a level of ∼0.4 mag (±0.05 mag), which corresponds to a precision of 18% in distances.…”
Section: Introductionsupporting
confidence: 76%
“…Many other works have used an updated version of the SCM where a color correction is added in order to take into account the hostgalaxy extinction. All these studies (Nugent et al 2006;Poznanski et al 2009Poznanski et al , 2010D'Andrea et al 2010;Olivares et al 2010;de Jaeger et al 2015) have confirmed the use of SNeII as distance indicators, finding similar dispersion in the Hubble diagram (0.25-0.30 mag). Recently, de Jaeger et al (2015) suggested a new method using corrected magnitudes derived only from photometry.…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Nugent et al 2006;Poznanski et al 2009). Techniques relying solely on photometric data are also being explored (de Jaeger et al 2015). The obvious advantage of being significantly less demanding in terms of the data required, comes A&A 592, A129 (2016) at the cost of lowered accuracy compared to the SCM.…”
Section: Introductionmentioning
confidence: 99%